Pengaruh Perputaran Piutang Terhadap ROA Studi Kasus PT. Bank Pembiayaan Rakyat Syariah Adeco - Jecky Ryan; Aswin Akbar (CIVITAS: Jurnal Studi Manajemen, 2022)
The purpose of this study is to determine whether the accounts receivable turnover affects the profitability of PT. BPR Syariah Adeco Langsa. The sample of this research is PT. Adeco SRB in 2016-2018, sampling using purposive sampling is a technique used to achieve certain goals. Data analysis using simple regression, hypothesis testing with the coefficient of determination (R2) test, partial test (t test), while processing data using SPSS 24. The results of research using the ttest is known that the pivot rotation variable has no effect on profitability at PT.Adeco Langsa SRB. Where the t-value for the Accounts Receivable Turnover variable is 0.171 <1.8124 and the significant value is 0.868> from alpha 0.05.